Market Democracy, Rising Populism, and Contemporary Ordoliberalism - Malte Dold; Tim Krieger (Center for Economic Studies and ifo Institute (CESifo), 2024)
Populist movements increasingly challenge liberal Western market democracies. Populism can be explained only in part by phenomena like globalization and digitization producing winners and losers in economic terms. Growing feelings of alienation from the market-democratic system and the perceived loss of autonomy within the political system contribute to rising populism as well. In this chapter, we ask whether elements of public deliberation may be a means to reasonably responding to the populist challenge by strengthening citizen sovereignty in addition to consumer sovereignty. Ordoliberalism, as a specific form of liberalism that aims at achieving both a 'functioning and humane order' within a system of 'interdependent orders', is particularly apt to embrace the idea of public deliberation if it is rules-based.
Keywords: B29; D63; D72; P16; 330; populism; ordoliberalism; democracy; deliberation